2004
DOI: 10.1073/pnas.0406933101
|View full text |Cite
|
Sign up to set email alerts
|

Role of a transductional-transcriptional processor complex involving MyD88 and IRF-7 in Toll-like receptor signaling

Abstract: Toll-like receptor (TLR) activation is central to immunity, wherein the activation of the TLR9 subfamily members TLR9 and TLR7 results in the robust induction of type I IFNs (IFN-␣͞␤) by means of the MyD88 adaptor protein. However, it remains unknown how the TLR signal ''input'' can be processed through MyD88 to ''output'' the induction of the IFN genes. Here, we demonstrate that the transcription factor IRF-7 interacts with MyD88 to form a complex in the cytoplasm. We provide evidence that this complex also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
357
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(379 citation statements)
references
References 31 publications
19
357
2
1
Order By: Relevance
“…Because the induction of type I IFNs is crucially dependent on the activation of IRFs, this raises the intriguing question of how these TLRs can activate IRFs without the help of TRIF. Plasmacytoid DCs show high levels of constitutive IRF7 expression, relative to monocyte-derived DCs [53], and two concomitant reports showed that Myd88 forms a complex with IRF7 to trigger its activation and induce IFN-a [54,55]. TLR7 and TLR9 are located primarily in the intracellular endosomal compartment [56,57] and the Myd88-IRF7 interaction takes place in the endosomal vesicles of the plasmacytoid DCs [58] (Figure 2).…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 93%
See 1 more Smart Citation
“…Because the induction of type I IFNs is crucially dependent on the activation of IRFs, this raises the intriguing question of how these TLRs can activate IRFs without the help of TRIF. Plasmacytoid DCs show high levels of constitutive IRF7 expression, relative to monocyte-derived DCs [53], and two concomitant reports showed that Myd88 forms a complex with IRF7 to trigger its activation and induce IFN-a [54,55]. TLR7 and TLR9 are located primarily in the intracellular endosomal compartment [56,57] and the Myd88-IRF7 interaction takes place in the endosomal vesicles of the plasmacytoid DCs [58] (Figure 2).…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 93%
“…The complex must remain in the endosome for a prolonged time period and resist transfer to lysosomal vesicles to trigger activation of IRF7 [58]. This complex also contains IRAK4 and TRAF6 and the ubiquitin ligase activity of the latter is required for IRF activation [54,55]. Furthermore, TLR7 and TLR9 ligands activate IRF7 in a Myd88-and IRAK-4-dependent manner.…”
Section: Tbk1 and Ikk-i Activate Irf3 And Irf7mentioning
confidence: 99%
“…Importantly, IRF7 interacts with MyD88, IRAK1 and TRAF6 to form a signaling complex (Figure 3). 65,66,70 Notably, IFNa production and IRF7 activation in response to TLR7 and TLR9 ligands are abolished in IRAK1-deficient pDCs. 70 Furthermore, in vitro experiments have clearly demonstrated that IRAK1, but not IRAK4, has an ability to phosphorylate IRF7.…”
Section: Activation Of Irfs By Tlr7/8 and Tlr9mentioning
confidence: 99%
“…While pDCs deficient of IRF3 normally respond to these TLRs, type I IFN and inflammatory cytokine induction is totally abolished in MyD88-and IRAK4-deficient pDCs. [64][65][66][67] Unlike other types of DCs, pDCs constitutively express high levels of IRF7. 68,69 Furthermore, treatment of pDCs with TLR9 ligands causes nuclear translocation of IRF7, and pDCs derived from IRF7-deficient mice are incapable of producing type I IFN in response to TLR7/8 and TLR9 ligands.…”
Section: Activation Of Irfs By Tlr7/8 and Tlr9mentioning
confidence: 99%
“…TLR3 signaling results in the activation of NF-kB and IRF3, ultimately leading to the production of antiviral molecules, such as type I interferons (IFN-a/b) (Alexopoulou et al, 2001). The importance of RIG-Iand MDA5-mediated viral recognition is further supported by gene-targeting experiments demonstrating that TLR3 and its adaptor TRIF are not required for type I IFN production in some virally infected cells, such as fibroblasts and conventional DCs (Honda et al, 2003). However, plasmacytoid DCs exclusively utilize TLR3/TRIF signaling for type I IFN production in response to RNA viruses and poly(I:C) .…”
Section: Viral Recognitionmentioning
confidence: 99%